2009
DOI: 10.1089/acm.2008.0093
|View full text |Cite
|
Sign up to set email alerts
|

A New Way: Alleviating Postembolization Syndrome Following Transcatheter Arterial Chemoembolization

Abstract: In conclusion, although single use of Dex or GS may improve some indices of adverse effects after TACE, the combination of Dex and GS can systematically prevent and treat the postembolization syndrome following TACE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…This was a well‐designed randomized, double‐blind, placebo‐controlled trial that modeled randomized controlled trials of prophylactic treatments for side effects of chemo therapy agents. For example, Yinglu et al conducted a prospective study that randomized subjects into four groups (i.e., placebo, placebo plus dexamethasone, ginsenosides and placebo, and ginsenosides plus dexamethasone) and reported that patients who received dexamethasone treatment (i.e., placebo plus dexamethasone or ginsenosides plus dexamethasone) experienced significantly less fever and nausea/vomiting than patients who were treated with placebo only . However, the trial design, such as the endpoints and the sample size as essentials of randomized control trials, was not appropriately reported.…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…This was a well‐designed randomized, double‐blind, placebo‐controlled trial that modeled randomized controlled trials of prophylactic treatments for side effects of chemo therapy agents. For example, Yinglu et al conducted a prospective study that randomized subjects into four groups (i.e., placebo, placebo plus dexamethasone, ginsenosides and placebo, and ginsenosides plus dexamethasone) and reported that patients who received dexamethasone treatment (i.e., placebo plus dexamethasone or ginsenosides plus dexamethasone) experienced significantly less fever and nausea/vomiting than patients who were treated with placebo only . However, the trial design, such as the endpoints and the sample size as essentials of randomized control trials, was not appropriately reported.…”
Section: Discussionmentioning
confidence: 42%
“…The incidence of abdominal pain, one of the common symptoms of postembolization syndrome, was significantly lower in the dexamethasone group compared with the control group in this study. A previous prospective study suggested that patients receiving dexamethasone had a significantly lower incidence of abdominal pain compared with patients receiving placebo . Taken together, these findings suggested that dexamethasone prevented pain by dampening inflammation after embolization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This double-blind RCT randomized patients to receive dexamethasone with or without ginsenosides versus placebo and reported statistically significant decreases in the incidence of RUQP in groups receiving dexamethasone versus ginsenosides alone. 10 Interestingly, Kogut and colleagues' 9 study of the benefit of steroid prophylaxis failed to reveal any significant differences between steroids and analgesic-based pain management. No analgesic agents were required in similar numbers of patients, regardless of the timing of the intervention, and the dose level and frequency of analgesic agent doses did not significantly differ between patient groups.…”
Section: Steroidsmentioning
confidence: 99%
“…Durations of PES of up to 2 weeks have also been reported. 10 Consequently, Basile et al 1 have now proposed considering PES to be an expected outcome of TACE.…”
mentioning
confidence: 99%